2012
DOI: 10.3389/fmicb.2012.00124
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Extracellular Superoxide on Iron Redox Chemistry and Bioavailability to Aquatic Microorganisms

Abstract: Superoxide, the one-electron reduced form of dioxygen, is produced in the extracellular milieu of aquatic microbes through a range of abiotic chemical processes and also by microbes themselves. Due to its ability to promote both oxidative and reductive reactions, superoxide may have a profound impact on the redox state of iron, potentially influencing iron solubility, complex speciation, and bioavailability. The interplay between iron, superoxide, and oxygen may also produce a cascade of other highly reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 136 publications
(208 reference statements)
2
79
0
Order By: Relevance
“…This could be explained by the fact that Mn 2ϩ has a higher reaction rate with superoxide than does iodide at a nearneutral pH (36). In addition to Mn 2ϩ , other metals, such as iron and copper ions, also exhibit higher reaction rates with superoxide than with iodide (36,39). In terrestrial environments (i.e., soils or groundwater), which typically contain higher concentrations of Mn 2ϩ or Fe ions (M to mM range) than iodide (low M), iodide oxidation mediated by superoxide may not be a significant pathway in bulk pore water.…”
Section: Discussionmentioning
confidence: 94%
“…This could be explained by the fact that Mn 2ϩ has a higher reaction rate with superoxide than does iodide at a nearneutral pH (36). In addition to Mn 2ϩ , other metals, such as iron and copper ions, also exhibit higher reaction rates with superoxide than with iodide (36,39). In terrestrial environments (i.e., soils or groundwater), which typically contain higher concentrations of Mn 2ϩ or Fe ions (M to mM range) than iodide (low M), iodide oxidation mediated by superoxide may not be a significant pathway in bulk pore water.…”
Section: Discussionmentioning
confidence: 94%
“…23,24 As demonstrated previously, superoxide produced from KO 2 25,26 or photoirradiated natural organic matter 27 can also reduce Ag + into AgNPs. Therefore, it is reasonable that superoxide bioproduced by microorganisms could reduce Ag + into AgNPs.…”
Section: ■ Introductionmentioning
confidence: 88%
“…It was reported that superoxide can be produced by bacteria and fungi. [19][20][21]23,24 Here, for the first time, we demonstrated the production of superoxide by F. oxysporum by using continuous flow CL (Figure 2). No CL signal was observed when only F.…”
Section: Environmental Science and Technology Lettersmentioning
confidence: 99%
“…The ability of O − 2 to influence the bioavailability of Fe in oxygenated waters by mediating its redox cycling has already been demonstrated under a range of scenarios (Kustka et al, 2005;Garg et al, 2007;Rose, 2012). Biologically produced extracellular O − 2 has also been shown to drive redox cycling of Mn in fungi (Hansel et al, 2012) and bacteria (Learman et al, 2011) under oxygenated conditions.…”
Section: Importance Of Ros For Local Redox Chemistry In Oxygenated Namentioning
confidence: 98%